Choices and Challenges: Moving from Junior Cycle to Senior Cycle Education - SMYTH, EMER (The Liffey Press in association with ESRI, NCCA and Department of Education & Skills)
This study examines the experiences of young people as they make the transition from junior cycle (lower secondary) to senior cycle (upper secondary) education. It is part of a series of reports which explore stu- dent experiences as they move through the second-level schooling sys- tem. In a companion volume (Smyth, Banks and Calvert, 2011), we ex- plore young people?s experiences of preparing for the Leaving Certifi- cate exams and for life after school, and highlight the skills and compe- tencies students feel they have gained from their education. Taken to- gether, the two reports provide crucial insights for policy development concerning senior cycle education. In systems where lower and upper secondary education are provided in different schools, transition experiences mirror the move from primary to secondary schooling, with students having new teachers, taking new subjects and adjusting to a new peer group (Wigfield et al., 1991; Dar- mody, 2008b). However, much less is known about what the transition is like for young people who remain within the same school setting, as they do in Ireland. Drawing on survey and interview data from Transition Year and fifth year students in twelve case-study schools, this study sets out to address this gap in knowledge by exploring the choices students make over the transition as well as their learning experiences and rela- tions with their teachers and peers. This executive summary outlines the main findings of the study and the implications for policy development.
PUBLISHED
Keywords: Education; Ireland